2021
DOI: 10.1002/cpt.2290
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of FAAH Inhibitor BIA 10‐2474: A Double‐Blind, Randomized, Placebo‐Controlled Study in Healthy Volunteers

Abstract: This study evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of BIA 10-2474, a fatty acid amide hydrolase (FAAH) inhibitor, after first administration to healthy male and female participants. Participants (n = 116) were recruited into this phase I, double-blind, randomized, placebo-controlled, single ascending dose and multiple ascending dose (10-day) study. The primary outcome was the safety and tolerability of BIA 10-2474. Secondary outcomes were pharmacokinetics of BIA 10-2474 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In this issue of CPT, 1 investigators from the company BIAL describe the ill‐fated experiment of 2016. The paper is co‐authored by company staff and two toxicology consultants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of CPT, 1 investigators from the company BIAL describe the ill‐fated experiment of 2016. The paper is co‐authored by company staff and two toxicology consultants.…”
mentioning
confidence: 99%
“…and its supplement that contains the various publications with (references to) preclinical data on BIA 10‐2474. 1 More information on the IB‐de‐risk process, as well as examples of compounds with acceptable IB‐profiles, can be found elsewhere. 4 We also included data from the human phase I clinical trials that were performed.…”
mentioning
confidence: 99%
“…This was perhaps best illustrated by the dissection of the tragic BIA 10-2474 trial in a recent issue of CPT. [5][6][7] The fact that this compound attrited in phase I was of course completely dwarfed by the fatal outcomes of the trial in healthy volunteers. Such cases are (thankfully) very rare, and therefore determining risk of harm (RoH) cannot rely on the Bayesian principles underpinning the PoS framework.…”
Section: Editorialmentioning
confidence: 99%
“…If all successes are not equal, we should also not forget that not all failures are the same and that probability of failure (PoF) cannot simply be defined as PoF = 1‐PoS . This was perhaps best illustrated by the dissection of the tragic BIA 10‐2474 trial in a recent issue of CPT 5–7 . The fact that this compound attrited in phase I was of course completely dwarfed by the fatal outcomes of the trial in healthy volunteers.…”
Section: Figurementioning
confidence: 99%
“…The well-conducted classical nonclinical safety studies together with a demonstrated absence of concerning findings in the early clinical evaluation of BIA 10-2474 4 seem to call for a re-examination and expansion of the International Council for the Harmonization of Technical Requirements for Pharmaceuticals (ICH) testing paradigm, and specifically, the S2(R1) Genotoxicity Testing guidelines finalized in 2011 5 and subsequently adopted by the FDA in 2012. 6 New guidelines should modify the protocols to include more comprehensive and powerful predictive toxicology, perhaps encompassing some specific genomic fingerprinting of the test organism/subject, with an eye to systematic interrogation of the data that illuminates possible interactions between the agent being evaluated and the genetically determined drug metabolomics of the host.…”
mentioning
confidence: 99%